A Survey of Speech Sound Productions in Children With Visual Impairments. (August 2019) - Gordon-Pershey, Monica; Zeszut, Shannon; Brouwer, Kyle
This survey addressed a twofold need: first, research into speech sound productions in children with visual impairments and, second, evidence upon which speech-language pathologists might base interventions for children with visual impairments. Fifteen speech-language pathologists responded to a survey about speech sound productions in caseload children with visual impairments. Respondents reported the speech characteristics of 46 children, their coexisting medical diagnoses and developmental conditions, the nature of their visual impairments, and therapy approaches used. Children and teens with visual impairments demonstrated speech sound production errors. It is not conclusive that errors resulted from having visual impairments. Respondents reported effective speech treatment techniques. This study contributes a detailed report of speech sound productions in children who, despite a diversity of coexisting diagnoses, had visual impairment in common. Findings provide a point of reference regarding speech sound productions in children with visual impairments, as well as efficacious treatments.